PERAN OPERATOR SEKOLAH DALAM MENGELOLA SISTEM DATA INFORMASI SEBAGAI PENJAMINAN MUTU PELAYANAN PENDIDIKAN DI SMP NEGERI 1 TELUKJAMBE TIMUR KARAWANG - Suryana Saputra (JS (JURNAL SEKOLAH), 2020)
Abstrak: Education now requires a foundation that must be built, namely realizing its position as a producer of educational services. Schools must understand well the needs of an increasingly complex society, especially followed by the rapid development of information IT. Research with the title "the role of school operators in managing information data systems as quality assurance of education services has the formulation of the problem what is the role of school operators in managing information systems as education quality assurance, the process of managing data and information systems as quality assurance, and what is the relationship between school operators and the process of managing data and information systems with the quality of education services in SMP Negeri 1 Telukjambe Timur the relationship of these variables with the quality of education services. The purpose of this study was to determine the role of school operators in managing information data systems as an assurance of the quality of education services, along with the relationships, school operators and the process of managing data and information systems with the quality of education services. The object of this study is focused on the role of school operators in managing information data systems as a guarantee of the quality of education services. This research is descriptive qualitative in nature based on as is. The results of this study that the role of operators in managing information data systems is an indicator of the quality of educational services. The relationship between them is symmetrical because the task of the service is not resting on the operator alone.Keywords: School Operators, Information Data System, Quality of Education servicesAbstract: Pendidikan saat ini membutuhkan dasar yang harus dibangun, yaitu menyadari posisinya sebagai penghasil jasa pendidikan. Sekolah harus memahami dengan baik kebutuhan masyarakat yang semakin kompleks terutama diikuti perkembangan IT informasi yang sangat pesat. Penelitian dengan judul “peran operator sekolah dalam mengelola sistem data informasi sebagai penjaminan mutu pelayanan pendidikan memiliki rumusan masalah apa peran operator sekolah dalam mengelola sistem data informasi sebagai penjaminan mutu pendidikan, Proses pengelolaan sistem data dan informasi sebagai penjaminan mutu, serta Apa hubungan operator sekolah dan proses pengelolaan distem data dan informasi dengan mutu pelayanan pendidikan di SMP Negeri 1 Telukjambe Timur hubungan dari variable tersebut dengan mutu layanan pendidikan. Tujuan penelitian ini untuk mengetahui peran operator sekolah dalam mengelola sistem data informasi sebagai penjaminan mutu pelayanan pendidikan, beserta hubungan, operator sekolah dan proses pengelolaan distem data dan informasi dengan mutu pelayanan pendidikan. Obyek penelitian ini terfokus kepada peran operator sekolah dalam mengelola sistem data informasi sebagai penjaminan mutu pelayanan pendidikan. Penelitian ini bersifat kualitatif deskriptif yang menggambarkan berdasarkan sebagaimana adanya. Hasil penelitian ini bahwa peran operator dalam mengelola sistem data informasi adalah indikator mutu pelayanan pendidikan. Hubungan diantaranya bersifat simetris karena tugas dari pelayanan bukan bertumpu pada operator saja.Kata Kunci: Operator Sekolah, Sistem Data Informasi, Mutu Pelayanan Pendidikan